The role of the muhammadiyah diaspora in global islamic education and the dissemination of progressive islam - Mustakim; Khozin; Muh Ahnaf Aqil; Faisal; Ngatmin Abbas (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study describes the role of the Muhammadiyah diaspora in supporting global Islamic education and spreading progressive Islamic values. The research was carried out with a qualitative approach through literature studies, by collecting data from various literature, official documents, and online databases, which were then analyzed using content analysis techniques. The findings show that the Muhammadiyah diaspora plays an active role in organizing formal, non-formal, and informal education that is adjusted to the social, cultural, and political situation of the community in the destination country. The da'wah strategy implemented includes academic, cultural, and digital approaches, so that the message of Islam that is moderate, inclusive, and contextual can be conveyed widely. On the other hand, they face challenges in the form of limited resources, differences of internal views, strict government policies against religious minority groups, and negative stigma against Islam in some countries. Nevertheless, the diaspora is able to maintain its identity by strengthening internal communication, fostering cadres in an ongoing manner, establishing cross-organizational cooperation, and adapting to local culture without ignoring the basic principles of Islam. This study concludes that the Muhammadiyah diaspora has succeeded in combining tradition and modernity in its role as an agent of spreading progressive Islam, as well as opening up space for further research on the contribution of the next generation of the diaspora in the future.